ANALYSIS OF COVID-19 LOCKDOWN POLICY IMPACT BY THE GOVERNMENT OF THE COUNTRY ON THE ECONOMIC SECTOR AND SIGNING OF WORKING RELATIONSHIPS (LAYOFFS) - Mohammed Abdela Mahammed (UNISSULA, 2020)
The lockdown authority based on the laws in each country regarding Health Quarantine is the absolute authority of the Government. As stated,